Organic liquid products from cracking of used cooking oils with commercial catalysts - Khajornsak Onlamnao (2020)
Copyright © 2020, AIDIC Servizi S.r.l. Catalytic cracking is widely used in biofuel production from natural fats and vegetable oils. Used cooking oils are one of the major wastes from food processing in Thailand. They are interesting raw materials to produce biofuel. This study focused on catalytic cracking of used cooking oils over two commercial (Z and Y zeolite) catalysts to generate light organic liquid products. The cracking reactor used was based on a fixed bed reactor setup. Temperature of reaction (400 °C) was controlled by a digital controller and a thermo-couple connected to the reactor. The liquid products obtained were subsequently analysed by gas chromatography and mass spectrometry. The maximum liquid yield of 82.5 % was obtained. From the chemical analysis, the organic liquid products were found to contain three (gasoline-, kerosene-, and diesel-like) groups with the carbon number between C7 – C11, C12 – C15, and C16 – C21.